Internists facing emerging arboviral diseases: time to get prepared - Emanuele Durante-Mangoni; Augusto Delle Femine; Raffaella Gallo; Ciro di Gennaro; the EFIM working group on Infectious Diseases in Internal Medicine (see supplementary file for list); Agnès Lefort des Ylouses; Jose Manuel Ramos-Rincon; Fausto Roxo; Michael Samarkos; Miriam Stegemann (Internal and Emergency Medicine, 2026)
Abstract Arboviral diseases are emerging and affect approximately 60 million individuals yearly. Climate change, vector migration patterns, urbanisation and global travel are boosting their spread beyond traditionally endemic regions, including Europe. This narrative review provides a practical and clinically oriented overview of the main arthropod-borne viral infections. We summarize their epidemiology, virological features, and transmission, highlighting shared as well as distinctive clinical presentations, diagnostic approaches and current management strategies. Although most infections are asymptomatic or self-limiting, severe complications may occur, including dengue haemorrhagic manifestations and shock, West Nile neuroinvasive disease, congenital and neurological complications of Zika, and chronic disabling arthritis after Chikungunya virus infection. Diagnosis remains challenging due to often nonspecific presentations, and laboratory interpretation may be complicated by timing of sampling and serological cross-reactivity. Since specific antiviral therapies remain largely unavailable, early clinical suspicion, appropriate laboratory testing, supportive care, vaccination (where applicable) and vector-control measures are central to patient management and public health response. Internists frequently evaluate patients with undifferentiated febrile illness in emergency departments and internal medicine units, and play a key role in the correct management of these infections, guiding differential diagnosis, identifying severe presentations, and supporting surveillance and prevention efforts in an era of expanding arboviral risk.